Principles of integrated disaster emergency response management in Indonesia - Hermansyah, Andi; Selvira, Rizka; Rahim, Abdur; Muksin, Zainal; Andriansyah (Universitas Islam Malang, 2024)
Disaster problems in recent years have become an interesting study, not only discussed by the government but also non-governmental organizations and the community. Facing this situation, the government must react and look for strategies to prevent natural (man-made) disasters or reduce the negative impacts following natural disasters.. Disaster phenomena can be studied from various scientific perspectives, including public administration. Disaster emergency response is a series of activities to deal with the direct negative impacts of disasters. According to BNPB Regulation Number 3 of 2018 concerning Handling Refugees in Disaster Emergency Situations, the Government's responsibilities in implementing Disaster Management include protecting the community from the impacts of disasters and ensuring the fulfillment of the rights of communities and refugees affected by disasters fairly and in accordance with minimum service standards. Based on the discussion above, it can be concluded that disaster management is part of a series implemented by the central and/or regional government through BNPB and/or BPBD in implementing post-disaster management or after a disaster by implementing in an integrated and comprehensive manner the principles that have been established which will implemented in stages determined by government regulations.